Lymph food to improve canine atopic dermatitis: a randomized, double-blinded, controlled trial in dogs with standard-care treatment - Frizzo-Ramos, Carolina; Doulidis, Pavlos G.; Burgener, Iwan Anton; Horvath Ungerböck, Christa; Einspieler, Veronika; Weiser, Ulrike; Panakova, Lucia; Roth-Walter, Franziska (Frontiers in Veterinary Science, 2025)
IntroductionMicronutritional deficits are linked to increased morbidity and mortality. Canine atopic dermatitis (CAD) often presents with iron depletion and subclinical inflammation, despite their typical meat-based diets, suggesting widespread micronutritional malabsorption. This study aimed to determine if a complementary lymph food—enriched with whey protein, vitamins, minerals, and antioxidants, and designed to bypass mucosal malabsorption barriers—could improve CAD clinical signs and blood parameters.AnimalsThirty-eight dogs diagnosed with canine atopic dermatitis were included in the study.MethodsIn a 112-day, double-blinded, randomized study, 38 CAD dogs daily received 10 g of either the active lymph food (n = 19) or a hydrolyzed food placebo (n = 19). Owners weekly recorded pruritus using the Pruritus Visual Analog Scale (PVAS) and logged medication use (Janus kinase inhibitors, corticosteroids, antihistamines, cyclosporine, and Lokivetmab). Veterinarians monthly assessed skin lesions via the Canine Atopic Dermatitis Extent and Severity Index (CADESI-4). Blood samples were collected at baseline and at the study's end. Treatment success was defined as a decrease of ≥2 on the PVAS and a ≥50% reduction in CADESI-4.ResultsThe complementary lymph food was well-accepted by the dogs. The active feed group showed significantly greater reductions in both CADESI-4 scores (−55%) and PVAS scores (−1.8) compared to the placebo group (+26%, p < 0.0003 and −0.05%, p = 0.0074, respectively), indicating an added benefit to standard care treatment. Medication use significantly declined in the active group. Furthermore, red blood cell counts, packed cell volume (PCV), and serum iron increased in the active group but not in the placebo group. A threefold significantly greater proportion of dogs in the active group achieved treatment success compared to the placebo group.ConclusionLymphatic nutrient feeding significantly improved CAD symptoms, suggesting a causative role of nutritional deficiencies in driving skin inflammation. This study strongly suggests a beneficial role for targeted lymphatic nutrient delivery in CAD management.